Bisexual Christian identity: a sociological exploration of the life stories of female and male bisexual Christians - Toft, Alex (2011)
This research project is an investigation into the lives of bisexual men and women who are also Christian. It is a sociological exploration of their identity and the negotiations which they undertake against the backdrop of a religion that sees their sexuality as a choice and fails to fully grasp the complexity of bisexuality, and a society that does not understand their sexuality. Bisexual Christians are an under-researched group, yet researching such a group can speak to sociological understandings of identity, sexuality and religion. This research project has found that identity is a complex negotiation between the private, public but also the situational/the context in which it occurs. Identity is a project of reflexive choice but within these confines and always with regard to the context in which they are being negotiated and done. Such negotiations take place around a ‘core’ identity which helps the respondents to feel grounded throughout. Bisexuality itself is misunderstood both within the secular and religious spheres. The research calls for bisexuality to be understood in terms of ‘dimensions’ of sexuality which carry different weightings for individuals, rather than producing a universal definition. Bisexuality challenges both monosexism and heterosexism that exists within secular and religious society. In terms of their religious lives the research has found that religious individualism and the ‘Turn to Life’ (Heelas and Woodhead 2005, Woodhead 2001) is more heightened within the lives of bisexual Christians because of the points highlighted above. Without any guidance and both a society and a religion which does not understand bisexuality, the respondents are left to creatively understand and give life and meaning to both their religious faith and their sexuality.